Media Literacy Among Santri Students Efforts to Build Originality and Credibility of Citizen Journalism - Mukoyimah; Ruhang; Qoidatus Syariah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research aims to determine the role of students in Islamic boarding schools in coloring information in the digital world so that the information produced is truly validated and to build the credibility of citizen journalism. The methodology used by the author is library research with a descriptive approach from a postpositivist perspective, namely observing all Islamic boarding school activities naturally and then explaining them in the form of descriptions, while for analysis, the author uses Miles Huberman data reduction, data presentation, and drawing conclusions. The author's research shows that the educational activities developed by this Islamic boarding school are ideal for meeting the requirements of citizen journalists. Because being a journalist not only requires knowledge of the tools but also the building of the information that will be conveyed. In Islamic boarding schools a person is taught science (Nahwu), Tool Science (Sharf), Arabic, Fiqh, Hadith, Akhlaq, Tarikh, Tajwid, Ulumul Qur'an, Ulumul Hadith, Ushul Fiqh, and Sufism. These sciences are able to support a person's knowledge in processing and producing information. Tool science can help someone skillfully write information to the public, by collaborating with religious sciences as a basis for considering morality, appropriateness, and even the effectiveness of messages.